An Analysis of Communication Strategies Applied by English Study Program Students in Speaking for Presentation - Gusti Komang Permana; Dedi Sofyan; Kasmaini Kasmaini (Journal of English Education and Teaching, 2019)
Abstract This Study was a mix method research which used the combination of both qualitative and quantitative data. This study was aimed to find out the types and the dominant communication strategies used by the fourth semester students of English Study Program in University of Bengkulu. The instruments used in this research were observation checklist adapted from Dornyei (1995) and video recorder to collect data. The data were analyzed by Dornyei’s Theory of Communication Strategies. The population of this study was fourth semester students of class A of English Study Program. The samples of this study were selected with purposive sampling technique. The findings of this research were: (1) the students used all types of communication strategies, namely: a) message replacement, b) topic avoidance, c) message abandonment, d) circumlocution, e) approximation, f) word coinage, g) non-verbal signal, h) literal translation, i) foreignizing, j) code switching, k) time gaining strategy, and l) appeal for help, and 2) the dominant type of communication strategies used by the students is time gaining strategy with 47.87%. The students mostly used time gaining strategy because they already have good proficiency but they still needed times or delays to produce the utterances.